Preemptive Versus Post Op Local Anesthetic Infiltration at Port Site in Gynae Surgery A Quasi-Experimental Study - Tayaba Tahira, Misbah Kausar Javaid, Shabnam Tariq, Nida Arif, Saima Saeed, Snober, (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Port-site pain is widely believed to cause postoperative pain in cases of gynecological laparoscopic surgery. cuts and leads to slow recovery and opioid overuse. Local anesthetic infiltration is an easy method to manage somatic pain in the areas of incision. The timing of infiltration, preemptive, or postoperative may affect analgesic efficacy. This study compared efficacy of preemptive and postoperative port-site local anesthetic. infiltration of postoperative pain reduction. Methodology: This is a quasi experimental study that was carried out at Lahore General Hospital, Lahore, between the months of November 2022 to October 2023. One hundred women who were having elective gynecological laparoscopic. surgery were recruited and separated into two groups of 50 patients. Group A received preemptive before skin incision, local anesthetic infiltration was given to Group B whereas infiltration occurred at the end of Group B. surgery. The pain measured after the operation with the help of the Visual Analog Scale (VAS) was 2, 6, 12, and. 24 hours. Total opioid consumption and time to first rescue analgesia were also recorded. Data were analyzed using independent samples t-test, repeated measures ANOVA, and chi-square test. Results: In the group that took preventative measures, pain scores were considerably lower at all postoperative intervals (p < 0.001). Repeated measures ANOVA showed a significant overall difference in pain trends between groups (p < 0.001). Mean opioid consumption was lower in the preemptive group (82.0 ± 24.5 mg vs 121.0 ± 30.2 mg; p < 0.001), and there was a greater delay in the onset of rescue analgesia (5.8 ± 1.9 hours versus 3.6 ± 1.5 hours; p < 0.001). Conclusion: Preemptive port-site local anesthetic infiltration provided superior postoperative analgesia and reduced opioid requirement compared to postoperative infiltration in gynecological laparoscopy. Keywords: Preemptive analgesia, Postoperative pain, Laparoscopy, Gynecological surgery, Local anesthetic infiltration, Port-site pain